Efficacy and safety of acupuncture for weight management: A systematic review and meta-analysis of randomized controlled trials - Yurou Li; Jingya Yang; Yuxiao Li; Hao Hu; Carolina Oi Lam Ung (Complementary Therapies in Medicine)
Introduction: Obesity is a chronic health problem worldwide, leading to an increased focus on weight management. Acupuncture is widely used in weight loss as traditional and complementary medicine because of its economy, simplicity, and safety. This study aimed to identify the latest evidence on acupuncture for weight loss and evaluate the efficacy and safety of the included randomized controlled trials (RCTs). Methods: Seven databases were searched to identify RCTs published since January 2013 on using acupuncture for weight management. The STRICTA, CONSORT, and Cochrane Collaboration’s Risk of Bias tools were used to evaluate the included trials’ quality and risk of bias. All eligible trials were included in this meta-analysis. Results: Sixty-four trials were included. Compared to control groups, acupuncture had a significant effect on BMI (mean difference (MD) = -2.15, 95 % confidence interval (CI) = -2.86 to −1.44, P < 0.01), body weight (MD = −2.67, 95 % CI = −4.07 to −1.28, P < 0.01), waist circumference (MD = −3.61, 95 % CI = −4.72 to −2.50, P < 0.01), and some blood test indicators. Serious adverse events were not observed. However, the quality of the included trials was generally poor, and the risk of bias was uncertain. Conclusions: Our study showed that acupuncture is effective for weight management. However, there are no clear conclusions regarding its safety. Studies of higher quality and longer duration are needed to improve the evidence base of acupuncture in weight management for clinical reference.